Maiolica of the Italian Renaissance - Kołodziejska, Ewa (ItaliAMO: Promotion of Italian Studies in the Academic and Non-Academic Environment, 2023)
Maiolica is an earthenware ceramic coated with a white, opaque tin glaze which was decorated with paints of a characteristic and rich color range. The aim of the article is to present the development of Italian maiolica in the 15th and 16th centuries. It presents the main centers producing maiolica and examples of their work. The production process and the analysis of the role and importance of Renaissance maiolicas were also included. The article discusses the problem expressed by the question: how did Italian maiolica evolve and what processes influenced its development? The presented conclusions are based on the results of qualitative analysis, primarily content analysis, as well as comparative analysis of selected maiolica products.